Diagnostic value of Peguero-Lo Presti electrocardiographic criteria for diagnosing concentric left ventricular hypertrophy in hypertensive patients at Dr. M. Djamil General Hospital Padang - Poedjijo, Yanuar Surya Saputra; Hanif, Akmal M.; Wahyudi; Murni, Arina Widya; Ahmad, Armen; Faheri, Eifel; Elvira, Dwitya; Kurniawan, Eka (Faculty of Medicine, Universitas Islam Indonesia, 2025)
Background: Hypertension is a risk factor for morbidity and mortality from cardiovascular disease. Left ventricular hypertrophy (LVH) is the main target organ due to hypertension, which is a predictor of the development of cardiovascular diseases such as heart failure. Echocardiography is the gold standard examination for determining heart geometry, and concentric LVH is often found in hypertensive patients. Electrocardiography (ECG) is a widely available, low-cost, and rapid modality for diagnosing LVH in healthcare facilities. The Peguero–Lo Presti (PLP) criteria in ECG examination have better sensitivity and specificity compared to other criteria. Objectives: This study aims to determine the diagnostic value of PLP ECG to diagnose concentric LVH.Methods: This research is an analytical observational study with a cross-sectional approach carried out at the inpatient installation of Dr. M. Djamil General Hospital Padang for 6 months, starting from April to September 2024. The study subjects who met the inclusion and exclusion criteria were 90 samples selected by consecutive sampling. An ECG examination was conducted using PLP criteria and echocardiography with the M-mode method to assess left ventricle (LV) geometry. Data were analysed using a 2x2 table to obtain sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and diagnostic accuracy.Results: From 90 samples, LVH geometry was found concentric in 65.50%, eccentric 4.40%, concentric remodelling 11.10%, and normal 18.90%. In the diagnostic test, PLP criteria had 79.66% sensitivity, 90.32% specificity, 94.00% PPV, 70.00% NPV, and 83.33% accuracy to diagnose concentric LVH in hypertensive patients.Conclusion: Peguero Lo-Presti criteria on ECG can be used for screening and early diagnosis of concentric LVH in hypertensive patients.